Effect of Lactobacillus Probiotic Supplement on Growth and Haematological Performance of Indian Major Carp Labeo rohita - Priyadharshini, J.; Margaret, I. Viji; Nisha, M. Barakath; Mohideen, R. Ajaz Haja (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The influence of probiotics bacteria Lactobacillus acidophilus improves the survival, growth, and Hematological performance of the Indian major carp Rohu (Labeo rohita). After acclimation, a 60-day experimental study was conducted with four different types of treatments; namely, T1: Control, i.e. Basal feed without Probiotic supplements, T2: Basal feed with Aeromonas hydrophila, T3: Lactobacillus supplemented probiotic feed without Aeromonas hydrophila, and T4: Lactobacillus supplemented probiotic feed with A. hydrophila. After the experimental study, growth parameters were monitored through Weight gain, Specific growth rates, survival percentage, and haematological parameters including WBC, RBC, haemoglobin (Hb), and haematocrit (Hct) values of probiotics treated group (T3 and T4) were significantly (P<0.05) higher than control and T2 group. The Present study indicated that the positive effects of the L. acidophilus probiotic supplement diet improved the survival, growth, and Haematological performance in aquaculture.